PROFIL, ALOKASI DAN PENDAPATAN TENAGA KERJA PADA PERKEBUNAN KELAPA SAWIT RAKYAT DI KABUPATEN SOLOK SELATAN - Yulistriani, Yulistriani; Mahdi, Mahdi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2017)
Labor is one of the main inputs in the production activities, including in agriculture. The quality and quantity of labor would have an impact on quality of products. Solok Selatan district is a new district in West Sumatera that has priority program for development of palm oil smallholders. The quality of labor will also determine the sustainability and success of the operational of palm oil smallholders.Field surveys and in-depth interviews had been carried out to find the profile, allocation and labor income of palm oil smallholders in Solok Selatan district. Respondents for this research were selected purposively with the criteria of land ownership is ? 2 hectares. This is because the farmers who have land area ? 2 Ha tend to use labor from outside the family and otherwise. The research finds that labors of palm oil smallholder in the research site were dominated by workers with primary education level (75%). Moreover, the average of work time allocation by respondents is was 84.5 HOK/ha/year. Meanwhile, the average income per month of the labors were Rp. 1,393,916.67 (flat land) and Rp. 1,786,083.33 - 1,837,333,33 (steep land) with assumption that each type of work available at any time and labors actively work for 8 hours per day in oil palm smallholder.